ANALISIS PENERAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP PROFITABILITAS PERUSAHAAN (STUDI KASUS PT HANJAYA MANDALA SAMPOERNA TBK) - Rohmah, Fauziyatur (Jurnal Akuntansi AKUNESA, 2013)
This purpose of research was to determine the company's ability to generate profitability before implementing Corporate Social Responsibility (CSR) after applying the Corporate Social Responsibility (CSR) in PT Hanjaya Mandala Sampoerna Tbk. This research uses ROA as a measure of profitability ratios. The sample used financial statements of PT Hanjaya Mandala Sampoerna Tbk before menerakan CSR in 1996-2000 and after implementing CSR in 2008-2012. Method data collection who used in this research is secondary data, which obtained from Bursa Efek Indonesia (BEI) and from official website company's. Method data analysis who used statistical test descriptive, Based on the results testing of statistic descriptive there are increase profitability after the application of CSR. Keywords: Corporate Social Responsibility (CSR), Profitability, Return on Asstes (ROA).